A multimodalidade no gênero charge: uma proposta situada na pedagogia dos multiletramentos - Silva , Janaína Patrícia Xavier dos Santos (2023)
Everyday, people are challenged to learn new ways of reading and understanding the different texts produced in the midst of advances in digital technologies and the massification of the internet. More and more, the interaction between words and images is perceived, making it essential to study these various modalities of languages or semioses, which have been transforming the traditional definition of text, demanding new reading skills and new literacies. Considering these new demands for reading multimodal texts within a Pedagogy of Multiliteracies, especially the reading of the textual cartoon genre, due to its wide use in schools and in large-scale national exams, such as ENEM, Prova Brasil and after the entrance exam for the Federal Institutes, an action research will be developed, centered on the challenges found in the practices of reading and understanding texts with greater visual information, as in the case of cartoons. The general objective of this research, therefore, aims to understand how multimodality can be explored in classes of the 9th grade of Elementary School, in the light of the Pedagogy of Multiliteracies, focusing on the development of reading competence. In this sense, a qualitative interventionist research was carried out in the Portuguese Language classes of the 9th grade of Elementary School, in a school located in the city of Nova Cruz-RN, in the second semester of the 2022 school year. The theoretical contribution on multimodality and multiliteracies is anchored in Rojo (2012, 2015, 2019), Ribeiro (2021), Cazden et al. (2021), Coscarelli (2016), Dionysus (2014); regarding reading comprehension, this research is based on Koch and Elias (2008) and Rojo (2012, 2015); and with regard to textual genres and charge, it is based on Dionísio (2010), Marcuschi (2008), Flôres (2002), among others. As data generation instruments, the conversation wheel and participant observation were used, which will be mobilized in the pedagogical workshops, and, for the analysis of the obtained data, the content analysis was adopted (BARDIN, 1977). Data analysis allowed us to understand that reading, not only verbal language but all the languages present in the texts (images, words, typography, facial expressions, gestures, sounds, colors, among others), in an integrated way, collaborate for a global comprehension of the texts. The phenomenon of multimodality and multiliteracies must be problematized in the daily lives of students and teachers and in works with textual genres, mainly based on communicative models that have a strong critical and argumentative content, as in the case of cartoons.